2010
DOI: 10.1002/lt.22157
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species mediate human hepatocyte injury during hypoxia/reoxygenation

Abstract: Increasing evidence shows that reactive oxygen species (ROS) may be critical mediators of liver damage during the relative hypoxia of ischemia/reperfusion injury (IRI) associated with transplant surgery or of the tissue microenvironment created as a result of chronic hepatic inflammation or infection. Much work has been focused on Kupffer cells or liver resident macrophages with respect to the generation of ROS during IRI. However, little is known about the contribution of endogenous hepatocyte ROS production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
118
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 41 publications
6
118
0
1
Order By: Relevance
“…Our group also has good experience with human hepatocyte isolation. 2 We have 2 points to raise with respect to this excellent study. The authors used human hepatocytes isolated from resected normal liver tissue in their study (51 cancer specimens and 39 specimens of benign etiology).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Our group also has good experience with human hepatocyte isolation. 2 We have 2 points to raise with respect to this excellent study. The authors used human hepatocytes isolated from resected normal liver tissue in their study (51 cancer specimens and 39 specimens of benign etiology).…”
mentioning
confidence: 95%
“…Our data show that such hepatocytes differ in their response to hypoxia and hypoxia/reoxygenation in comparison with hepatocytes isolated from normal livers. 2 Did the authors note any phenotypic differences between hepatocytes isolated from cancer specimens and those isolated from benign livers? Moreover, did this have a bearing on transplant success?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Our recent study has conclusively shown that hepatocytes are also important sources of ROS during hepatic IRI. 4 This latter point has not been included in the review by Abu-Amara et al Indeed, hepatocytes may also be important sources of ROS along with Kupffer cells and neutrophils in the late stage of hepatic IRI. 2 We suggest that models of hepatic IRI should include the significant contribution of hepatocytes to the evolution of the injury.…”
mentioning
confidence: 99%
“…First, hepatocytes generate significant levels of intracellular ROS during hypoxia and hypoxia/reoxygenation. 4 The subsequent release of intracellular ROS by necrotic hepatocytes into the liver parenchyma will perpetuate hepatocyte cell death. 5 Second, hepatocytes can secrete proinflammatory cytokines and chemokines during hepatic inflammation, which can then propagate liver injury.…”
mentioning
confidence: 99%